ZAKAT DIGITAL DI ERA MODERN: KAJIAN ANALISIS BIBLIOMETRIK - Ali Abdurroziq; Akbar Dimas Satria; Reza Novriwanda; Solahuddin Al-Ayubi (Mumtaz Publishing, 2024)
This research aims to identify digital zakat research trends in the modern era and identify the most widely discussed research topics. This research highlights the importance of digital zakat in increasing the transparency, efficiency and impact of zakat. In this research the author used a bibliometric analysis method with data in the form of research journals and other research publications related to digital zakat in the modern era published within the last 10 years. The results of this research also identify topics and keywords that are often discussed, collaboration of researchers involved in digital zakat research. The conclusions of this research confirm the relevance of digital zakat in the modern era and provide insight into research trends and researcher collaboration in this field.